Cleo Fariselli - Your storm, our dew - Martínez, Chus 1972-; Santandrea, Guido (Viaindustriae Publishing, 2023)
This first monograph dedicated to the work of Cleo Fariselli recounts the poetic and formal processes behind the moving image project Your Storm Our Dew (2023), which explores the contemporary collective unconscious at a time when states of emergency have become normalized. The artist transforms everyday items such as thermal blankets, protective suits, high-visibility vests, safety cones, and megaphones into creature that belong in the world of YSOD. These beings are both playful and unsettling, as seen in the large puppets that, illuminated by sudden flashes of light, emerge from the darkness of their habitat only to disappear again shortly afterwards to the amazement of those watching. Expanding upon the film, the contributions by Lucia Aspesi, Cleo Fariselli, Chus Martinez, and Guido Santandrea shed new light on the artist’s multidisciplinary practice. At the same time, they explore the shadows of anthropocentric thinking at the intersection of art and science, ultimately asking how the past and the present inform the futures of our imagination. Exploring the imaginative power of the object elements typical of states of emergency, the artist gives life to a world of its own, illumi nated by the incessant flashing of sirens, creating a new emotional, narrative and aesthetic environment
Print run: 500 copies
Keywords: Fariselli, Cleo -- 1982-; Geschichte 2023; Videokunst; Fariselli, Cleo / Your storm our dew; Video art / Italy / 21st century; Art vidéo / Italie / 21e siècle; Interview